Minerals Availability from Grazing Resources to Livestock in Arid Soils - Mathur, B K; Sirohi, A S; Bohra, R C; Patidar, M P; Thada, Monika; Patidar, Tejkaran; Bairwa, Mukesh; Jat, S R; Misra, A K; Kumawat, R N (Annals of Arid Zone, 2017)
The present study was conducted to estimate the mineral contents of grazing resources grown on arid soils for their availability to livestock. The grazing/browse resources were mostly weeds, grasses, shrubs and trees. Under this study 20 mature and dry plant samples along with twigs, comprising 7 weeds and 4 grasses, 5 shrubs and 4 trees commonly preferred for grazing by livestock were collected by hand plucking from CAZRI farm, as well as adopted villages of Barmer and Jaisalmer districts in western Rajasthan during 2010-2012. These weeds, grasses, shrubs and trees samples were analyzed for minerals namely Ca, Fe, Zn, Cu, Co, Mn, Cr, Pb and Mo. The mineral content (Î¼g 100 g-1 except Ca, which is in mg 100 g-1) in weeds, grasses, shrubs and trees ranged between 105.63 (Cenchrus setigerus - Grass) and 412.57 (Capparis decidua - Shrub) for Ca, 91.67 CC-CAZRI-392 (Cenchrus ciliaris - Grass) and 151.50 (Calotropis procera - Shrub) for Fe, 202.43 CC-CAZRI-358 (Cenchrus ciliaris - Grass) and 583.30 (Achyranthes aspera - Weed) for Zn, 61.53 (Lasiurus sindicus - Grass) and 241.63 (Tetrapogon tenellus - Weed) for Cu, 27.16 (Calotropis procera - Shrub) and 118.63 (Cordia gharaf - Shrub) for Co, 26.03 (Cordia gharaf - Shrub) and 89.85 (Ziziphus nummularia - Shrub) for Mn, 42.80 CC-CAZRI-358 (Cenchrus ciliaris - Grass) and 289.26 (Digera muricata - Weed) for Cr, 19.08 (Lasiurus sindicus - Grass) and 130.27 (Prosopis cineraria - Tree) for Pb and 0.62 (Cenchrus setigerus - Grass) and 113.84 (Tribulus terrestris - Weed) for Mo. In comparison to grasses, shrubs and trees, the availability of minerals from weeds is higher.